PENGARUH MODEL BISNIS DIGITAL TERHADAP KINERJA USAHA MIKRO DAN KECIL SEKTOR KULINER DI KOTA PADANG: Efek Mediasi dari Pembaruan Bisnis - Dian Harja; Donard Games; Dessy Kurnia Sari (Journal Publicuho, 2024)
This study aims to empirically prove the effect of digital business models on the performance of Micro and Small Enterprises (MSEs) in Padang City and the role of business renewal in strengthening the relationship. A total of 170 MSEs in the culinary sector that have been digitized for at least two years and are domiciled in Padang City were used as research samples. Data were collected through distributing questionnaires, and data analysis was carried out using quantitative methods with path analysis. The results of hypothesis testing show that the digital business model has no direct significant effect on financial performance or non-financial performance. In contrast, business renewal has a positive and significant influence on financial performance and non-financial performance. In addition, digital business models also have a positive and significant effect on business renewal. The indirect effect of digital business models on financial performance through business renewal is significant, but its indirect effect on non-financial performance through business renewal is not significant. Overall, this study confirms the importance of business renewal in mediating the relationship between digital business models and MSEs' financial performance. Although the digital business model does not have a significant direct effect on financial and non-financial performance, it is not significant.